Critical Analysis of Emerging Technologies in Laboratories and Their Role in Disease Detection - Alzibarah, Mohammed Hamad; Al-Zubaid, Abdulrahman Hassan; Alhareth, Bader Salem Al; Al Asiri, Yahya Ahmed Mohammed; Al Bahri, Abdullatif Naqtan; Al-Sehab, Abdullah Mohammed Hussein; Almashaham, Ibrahem Ahmad Ali; Alsulaiman, Mohammed Saleh Ali; Al Mnsoore, Hadi Mohammad Saleh; Al abbas, Hamad Yahia Asker (Journal of Ecohumanism, 2024)
This research work, therefore, seeks to critically evaluate the use of emerging technologies in laboratories and, more particularly, the use of such technologies in the diagnosis of diseases. Therefore, in recent years, healthcare diagnostics and monitoring have received a boost from the revelation of laboratory technologies. Investments have been made in genetic sequencing systems, AI-assisted diagnostics, CRISPR-associated gene-editing tools, and portable diagnostic devices—all of which are changing the field of medical labs for the better to one that offers faster, more accurate diagnostic capabilities and less invasiveness. The advantages, challenges, and possible future applications of these technologies for enhancing the detection of diseases are also discussed, thereby giving the overall consideration of the benefit to the larger society. This paper draws on qualitative data, case avatars, and global examples and scenarios in order to evaluate the state and potential of molecular diagnostics in the identification of diseases in laboratories.